Armoede, gender, seks, en de Bijbel - Punt, J. (Kerk en theologie, 2024)
Poverty, gender and sex, and biblical interpretation are informed and impacted by a long interpretive history and constitute various hermeneutical challenges. Notwithstanding terminological and definitional difficulties regarding poverty, its intersectionality with gender is vital for accountable and responsible hermeneutics. Poverty and gender intersected particularly within ancient households, and poverty and sex in ancient prostitution - and in both cases, not without interesting considerations for the modern-day context. In a final section, some suggestions are made regarding the value of investigating the intersection(s) of poverty, gender and sex in biblical interpretation, for the past and present.